Propuesta para fortalecer el sistema de gestión de la calidad organizacional en una entidad financiera del sector público colombiano (2019)
Continuous improvement means optimizing the effectiveness and efficiency to respond to needs of customers associated with products and services, it is a challenge for any organization. As a general rule public entities must comply with the Quality Management System (SGC) established in the NTCGP 1000: 2009 standard. However, as in the case of the entity subject of this paper, based on historical information and a perception instrument, deficiencies were evident, given the lack of a continuous improvement specific methodology and weaknesses in people management regarding the quality culture, causing non-compliance of the standard’s requirements and principles, this also has affected some processes effectiveness, as well as the satisfaction of the citizen, aspect represented in an average claims per year between 7,000 and 8,000 and about 1,800 findings in the last six years with the aggravating circumstance of not being handled in time or in some cases not having the improvement adequately covered. From the aforemetioned, this project aimed to design a proposal that will lead to the processes effectiveness improvement to deliver products and services that meet the client’ expectations. The proposal developed has three phases: diagnosis of the QMS, improvement management team, improvement process design and implementation and a transversal axis of quality culture management. Each phase is supported by a set of methods and techniques. As a result of its application, the organization must improve its activities efficiency, represented in better citizen satisfaction rates.